1963
DOI: 10.2514/3.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exhaust Nozzle Recombination on Hypersonic Ramjet Performance

Abstract: Exhaust nozzle recombination studies are carried out for hydrogen-fueled subsonic combustion ramjet engines. Bray's criterion is used to determine a nozzle freezing point. Nozzle performance is calculated by assuming equilibrium conditions up to the freezing point and frozen flow from the freezing point to the nozzle exit. Several engine parameters are varied in order to determine their effect on recombination and specific impulse. These parameters include nozzle throat size, throat radius of curvature, nozzle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…5, the ratio was 0⋅956. This is in accord with previous investigations (3)(4)(5)(6)(7) , where nozzle freezing caused only a small loss in thrust.…”
Section: Numerical Modellingsupporting
confidence: 93%
See 1 more Smart Citation
“…5, the ratio was 0⋅956. This is in accord with previous investigations (3)(4)(5)(6)(7) , where nozzle freezing caused only a small loss in thrust.…”
Section: Numerical Modellingsupporting
confidence: 93%
“…An early study (3) of freezing of hydrogen-air chemical recombination in a ramjet thrust nozzle, where the expansion takes place from a low subsonic Mach number, showed that if equilibrium flow is maintained past the low supersonic area ratios the loss in thrust caused by chemical freezing is not exceedingly high. In later numerical studies of scramjet thrust nozzles at high flight Mach numbers, where the nozzle expansion takes place from supersonic Mach numbers, it was shown that although molecular vibration was in equilibrium throughout the nozzle, the chemical composition was not (4) , that at precombustion pressures of the order of an atmosphere there was little recombination in the nozzle (5) and that, in spite of this, the lack of complete recombination yielded an overall thrust which was only 1% less than the value for an equilibrium expansion (6) .…”
Section: Introductionmentioning
confidence: 99%
“…The exhaust-nozzle flow was assumed to be in equilibrium. 11 As indicated in Fig. 1, the second stage was considered to be carried internally.…”
Section: Analysis Modelmentioning
confidence: 99%
“…It is finally important to note that the thermodynamic-consistency condition (40), that the entropy generation rate be non-negative definite under the endogenous dynamics, is always satisfied, because in evaluating the ratesċ τ i we use the full internal dynamics (the detailed kinetic scheme), with forward and reverse rate constants k + and k − that depend on temperature and pressure only, a condition that we have seen in Section 4.6 warrants the nonnegativity of the entropy generation rate. As previously noted (see also [53,76]), whether or not there are kinetically-controlled constraints in addition to element conservation, all conceivable reactions contribute to the rate of entropy production.…”
Section: Rate-controlled Constrained-equilibrium Formulation For a CLmentioning
confidence: 99%
“…Sugden and co-workers [37], Kaskan [38], Schott [39], and Franciscus and Lezberg [40] treated the hydrogen-oxygen combustion problem. Keck and Gillespie [41] (see also [42,43]) developed a general rate-controlled constrained-equilibrium method for reacting gas mixtures.…”
Section: Introductionmentioning
confidence: 99%